Growth and Development of Islam in Sumatra (Literature Review on the 3 Islamic Kingdoms in Sumatra) - Shafiah Shafiah (Al-Madrasah: Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This research aims to understand the early introduction of Islam to Sumatra and the Islamic kingdoms in the region by examining the history of religious and governmental development in the area. The research utilizes a combination of literature review and historical analysis approaches. The findings indicate that 1) Islam has been present in this region since an early period. Muslim traders, preachers, and religious teachers from various regions such as Arabia, India, Persia, and China played a crucial role in spreading Islam in Sumatra. The Islamic kingdoms of Samudera Pasai, Aceh, and Minangkabau serve as evidence of the significant development of Islam in the region. 2) The history of Islamic development during the Islamic kingdoms in Sumatra is as follows: a) During the reign of Samudera Pasai, the kingdom became a center for Islamic studies and a gathering place for scholars from various Islamic countries to discuss religious and worldly matters. b) The Aceh Darussalam Kingdom became a center for the development of Islam in Indonesia during the reign of Sultan Iskandar Muda. In Aceh, the Baiturrahman Mosque, places of worship, and Islamic study institutions were built. c) During the era of the Minangkabau Islamic Kingdom, many aspects of customary practices that contradicted Islamic teachings were gradually eliminated, and the fundamental rules of customs were replaced with Islamic principles. The famous Minangkabau adage, "Adat basandi syarak, syarak basandi Kitabullah," means that Minangkabau customs are based on Islam, which in turn is based on the Quran and Hadith.